(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: The present case-control study was conducted to assess the prevalence and pattern of oral diseases among patients with diabetes. Methods: The study was conducted at the Department of Dentistry, Shaheed Khalek-Ibrahim General Hospital (An Institution of Diabetic Association of Bangladesh), Dhaka, from April to September 2010 using a case-control design. A total of 100 subjects— 47 diabetics and 53 non-diabetics— who met the eligibility criteria were consecutively selected from outpatient attendees. Diabetic status was confirmed, and controls were free of diabetes. Data on socio-demographics, oral health practices, and clinical oral conditions were collected and analyzed. Results: Diabetic patients were significantly older than controls (p<0.001), although there was no significant difference in terms of sex distribution and residential status between groups (p=0.194, p=0.138 respectively). Diabetics had a lower socioeconomic status and education level (p=0.004 and p=0.010, respectively) compared to their non-diabetic counterparts. Oral health disparities included higher prevalence of gingivitis (78.7% vs. 37.7%, p><0.001), periodontitis (48.9%), alveolar bone loss (29.8%), and collagen metabolism disturbances (27.7%) in diabetics, none of which were observed in controls (p><0.001). Diabetics also had higher rates of candidiasis and dental caries (p=0.020 and p><0.001). Conditions such as glossodynia, salivary dysfunction, taste impairment, xerostomia, and burning mouth syndrome were predominantly observed among diabetics. Oral hygiene practices were similar in both groups, although fluoridated toothpaste use was lower among diabetics (p=0.002). Diabetic patients infrequently visited dentists for routine care (12.8%), with many seeking treatment for restorations and cleaning> <0.001) although there was no significant difference in terms of sex distribution and residential status between groups (p=0.194, p=0.138 respectively). Diabetics had a lower socioeconomic status and education level (p=0.004 and p=0.010, respectively) compared to their non-diabetic counterparts. Oral health disparities included higher prevalence of gingivitis (78.7% vs. 37.7%, p<0.001), although there was no significant difference in terms of sex distribution and residential status between groups (p=0.194, p=0.138 respectively). Diabetics had a lower socioeconomic status and education level (p=0.004 and p=0.010, respectively) compared to their non-diabetic counterparts. Oral health disparities included higher prevalence of gingivitis (78.7% vs. 37.7%, p><0.001), periodontitis (48.9%), alveolar bone loss (29.8%), and collagen metabolism disturbances (27.7%) in diabetics, none of which were observed in controls (p><0.001). Diabetics also had higher rates of candidiasis and dental caries (p=0.020 and p><0.001). Conditions such as glossodynia, salivary dysfunction, taste impairment, xerostomia, and burning mouth syndrome were predominantly observed among diabetics. Oral hygiene practices were similar in both groups, although fluoridated toothpaste use was lower among diabetics (p=0.002). Diabetic patients infrequently visited dentists for routine care (12.8%), with many seeking treatment for restorations and cleaning> <0.001), periodontitis (48.9%), alveolar bone loss (29.8%), and collagen metabolism disturbances (27.7%) in diabetics, none of which were observed in controls (p<0.001). Diabetics also had higher rates of candidiasis and dental caries (p=0.020 and p><0.001). Conditions such as glossodynia, salivary dysfunction, taste impairment, xerostomia, and burning mouth syndrome were predominantly observed among diabetics. Oral hygiene practices were similar in both groups, although fluoridated toothpaste use was lower among diabetics (p=0.002). Diabetic patients infrequently visited dentists for routine care (12.8%), with many seeking treatment for restorations and cleaning.> <0.001). Diabetics also had higher rates of candidiasis and dental caries (p=0.020 and p<0.001). Conditions such as glossodynia, salivary dysfunction, taste impairment, xerostomia, and burning mouth syndrome were predominantly observed among diabetics. Oral hygiene practices were similar in both groups, although fluoridated toothpaste use was lower among diabetics (p=0.002). Diabetic patients infrequently visited dentists for routine care (12.8%), with many seeking treatment for restorations and cleaning. Conclusion: Diabetes is associated with an increased prevalence of infectious, inflammatory, and neurosensory oral disorders. Gingivitis, candidiasis, and dental caries are particularly common, alongside mucosal symptoms like glossodynia and xerostomia. Enhanced interdisciplinary dental and medical management is essential to mitigate these oral health complications in diabetic individuals. Ibrahim Card Med J 2024; 14 (2): 54-59